Studi Sytematic Review: Faktor Yang Mempengaruhi Food Waste Global Dalam Perspektif Hifzhul Bi'ah - Romadhan, Raid Azhar; Fitria Idham Chalid; Rosiatun Khasanah (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
This systematic review study analyzes the factors influencing food waste in various countries from the perspective of Hifzhul Bi'ah. The problem of food waste is a significant challenge because it impacts global food availability. From an Islamic ethical perspective, this phenomenon contradicts the principles of Hifzhul Bi'ah (Environmental Jurisprudence), which aims to realize the public good and prevent damage (israf) on earth. This study used a Systematic Review method based on PRISMA guidelines, reviewing 15 articles published between 2020–2025, predominantly from Indonesia. Most studies applied the Theory of Planned Behavior (TPB) and Structural Equation Modeling (SEM PLS) methodology. Key factors that consistently influence food waste are Attitude, Subjective Norms, and Behavioral Control, as well as additional factors relevant to the moral aspects of Hifzhul Bi'ah, such as Religiosity and Environmental Awareness. The findings indicate that food waste is a multifactorial phenomenon, involving internal psychological/moral and external social/economic dimensions. A holistic and contextual mitigation strategy is needed, which explicitly integrates the sharia guidance of Hifzhul Bi'ah, to encourage sustainable anti-waste behavior and support the achievement of the SDGs